2014
DOI: 10.1007/s11104-014-2277-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil C:N ratio is the major determinant of soil microbial community structure in subtropical coniferous and broadleaf forest plantations

Abstract: Aims This study aimed to determine the influence of tree species on soil microbial community structure. Methods We conducted a litter and root manipulation and a short-term nitrogen (N) addition experiment in 19-yearold broadleaf Mytilaria laosensis (Hamamelidaceae) and coniferous Chinese fir (Cunninghamia lanceolata) plantations in subtropical China. Phospholipid fatty acid (PLFA) analysis was used to examine treatment effects on soil microbial community structure. Redundancy analysis (RDA) was performed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
96
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(117 citation statements)
references
References 58 publications
16
96
3
2
Order By: Relevance
“…On the other hand, Ascomycota is one of the most abundant fungal phyla, which is able to access nutrition through various means, including saprophytic, parasitic, and symbiotic methods. In addition, N is the main source for microbial nutrition in soil [25], taking part in the synthesis of proteins, nucleic acids, and macromolecular substances as well as supplying a large number of essential elements for microbial growth and its metabolic processes [26]. At the same time, N also plays an important role in the material cycle, energy flow, and multi-element balance of ecosystems and its effect on microbial growth exceeds that of soil pH and other environmental factors [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ascomycota is one of the most abundant fungal phyla, which is able to access nutrition through various means, including saprophytic, parasitic, and symbiotic methods. In addition, N is the main source for microbial nutrition in soil [25], taking part in the synthesis of proteins, nucleic acids, and macromolecular substances as well as supplying a large number of essential elements for microbial growth and its metabolic processes [26]. At the same time, N also plays an important role in the material cycle, energy flow, and multi-element balance of ecosystems and its effect on microbial growth exceeds that of soil pH and other environmental factors [27].…”
Section: Discussionmentioning
confidence: 99%
“…Luo [32] used the DGGE method to study soil microbial communities of long-term fertilized soils, reporting that fertilization changed both soil C/N and microorganism community structure, and both had a significant correlation. Wan [33] used the PFLA method to study the relationship of soil microorganism community and soil pH and C/N in a Swedish boreal forest, and found that changes in soil C/N significantly affected the soil microbial community structure, thereby affecting the nitrogen supply to plants. Finally, Ushio et al [34] reported that the C/N and soil microbial community structure were different in coniferous and broadleaf forests and that the types of returned soil organic matter could cause changes in soil properties and microbial community composition.…”
Section: The Soil Fungal Community Structure Similarity Of Different mentioning
confidence: 99%
“…These invasive plants are ultimately the cause of higher soil C:N ratios relative to the native ecosystem16. The soil C:N ratio is a primary driver for the alteration in the soil microbial community structure17. The fungal biomass is highly associated with soil C:N ratio, whereas the bacterial biomass is negatively correlated with soil C:N ratio1718.…”
mentioning
confidence: 99%
“…The soil C:N ratio is a primary driver for the alteration in the soil microbial community structure17. The fungal biomass is highly associated with soil C:N ratio, whereas the bacterial biomass is negatively correlated with soil C:N ratio1718. The response of the soil microbial community structure and activity to plant invasion exhibits high variation, probably as a result of the diverse changes of soil C sources and nutrient availability following invasion of distinct plant species810.…”
mentioning
confidence: 99%